Analysis of dislocation, relocation, and financial valuation of energy companies of lithium and gas affected by Russia - Ukraine conflict - Flores Gálvez, Jessica Nallely; Hernández Mendoza, Abdiel; Mata Hernández, José Miguel (Papeles de Europa, 2024)
The research confirms that lithium and natural gas-focused energy companies were affected by the Russia-Ukraine conflict in 2022. However, gas companies exacerbated their problems during the COVID-19 pandemic. The following paper measures the financial impacts of lithium and liquefied natural gas companies listed on international stock exchanges, to determine if they should consider relocating or dislocating. The Tobin Q, Z Score, and Dupont Extended methods were used to perform the analysis.Additionally, the results show that some companies are facing financial difficulties, and their share prices are higher than their actual capital. This suggests a decision-making scenario for companies to either relocate or restructure their operations for better control. Futhermore, lithium companies obtained better returns than gas companies as a result of the situation. Therefore, lithium entities have better feasibility to dislocate, while gas companies have a greater viability to do relocation.
Keywords: Tobin’s Q; Z score; Russia-Ukraine conflict; lithium; gas